2003
DOI: 10.1080/1065657x.2003.10702143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Organic-Based Fertilizer To Mineral Fertilizer on Tomato Growth and Fruit Yield

Abstract: The effect of three different organic based fertilizers (OBF) was compared to conventional chemical fertilizer on tomato (Lycopersicon esculentum). The OBF is composted plant material fortified with poultry manure. The compost used was made from Maize (MP), guinea grass (GP) and cowpea (CP) stovers in combination with poultry manure in ratio 3:1 by weight. Two rates of each compost type (4t/ha, and 2t/ha + 30kgN/ha), the recommended rate of mineral fertilizer (i.e. 60kg N/ha) and nonfertilizer control plants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 4 publications
4
12
0
Order By: Relevance
“…Increases in the vegetative growth of tomato plants by applying chicken manure might be referred to its role in enhancing soil physical prosperities as soil texture, water holding capacity and it creates good aeration in soils and decreased the pH value and consequently nutrients in the soil became more available for enhancing plant growth. This result is in agreement with Togun and Akanbi (2003), Adenawoola and Adejoro (2005), Ewulo et al (2008) and Ayeni et al (2010).…”
Section: Effect Of Chicken Manure + Bio Mixturesupporting
confidence: 92%
“…Increases in the vegetative growth of tomato plants by applying chicken manure might be referred to its role in enhancing soil physical prosperities as soil texture, water holding capacity and it creates good aeration in soils and decreased the pH value and consequently nutrients in the soil became more available for enhancing plant growth. This result is in agreement with Togun and Akanbi (2003), Adenawoola and Adejoro (2005), Ewulo et al (2008) and Ayeni et al (2010).…”
Section: Effect Of Chicken Manure + Bio Mixturesupporting
confidence: 92%
“…This result could be due to both mineral phosphorus fertilisation (50 kg P 2 O 5 ha -1 year -1 ) for all treatments tested and municipal solid waste compost content for the Ncompost treatment. The exchangeable potassium decreased in all experimental treatments, especially in the control (93.0 mg kg -1 equal to 9.8%) and in Nmineral (9.7%) treatments compared with Ncompost (6.0%), strengthening the potential of mineral fertilisation of municipal solid waste compost (Giusquiani et al, 1988;Eriksen et al, 1999;Togun and Akanbi, 2003). No increase in the total content of heavy metals and other elements (Na, Mg and Ca) was found in the Ncompost treatment at the end of the two-year experiment, although a slight, but not significant, increase was observed for lead content.…”
Section: Soil Characteristics and N Mineral Deficitmentioning
confidence: 99%
“…Idah and others [17] treated Roma cultivar using chemicals and revealed that moisture was lower in control plants than that in chemically treated groups. Togun and Akanbi [18] used different types and doses of fertilizers on tomato plants and found that the dry matter accumulation increased in tomato fruits. However, the difference between control and treatment groups was not significant.…”
Section: Effect Of Stimplex On Moisture Contentmentioning
confidence: 99%